1964
DOI: 10.5006/0010-9312-20.4.111t
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Iron from Aqueous Solutions Onto an Aluminum Alloy

Abstract: Heavy metal contaminants such as copper, nickel and cobalt have long been recognized as corrosion hazards in aqueous solutions because their reduction is a comparatively common electrochemical corrosion reaction. It has been known for many years that Fe (III) is corrosive to various metals if the ferric salt is soluble, that is, if the solution is sufficiently acid to maintain the Fe (III) ion in solution. Metals such as aluminum, zinc, cadmium, iron, etc., reduce Fe (III) to Fe (II). Furthermore, if dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Especially relevant in this regard is the work described by Cook and McGeary (1964). They showed that Fe is also able to deposit on an Al-alloy substrate from a concentrated chloride brine solution and increase the corrosion rate of the underlying alloy if the solution is anoxic and if the iron present in the solution is in the form of ferrous ion.…”
Section: -1mentioning
confidence: 96%
See 1 more Smart Citation
“…Especially relevant in this regard is the work described by Cook and McGeary (1964). They showed that Fe is also able to deposit on an Al-alloy substrate from a concentrated chloride brine solution and increase the corrosion rate of the underlying alloy if the solution is anoxic and if the iron present in the solution is in the form of ferrous ion.…”
Section: -1mentioning
confidence: 96%
“…This rationale does not imply an understanding of the reasons for the sensitivity of high-purity aluminum to anoxic brine containing Fe++ and the lack of sensitivity of the 6061 alloy. It could be related to the ability to reduce Fe++ to metallic Fe on the AI-base material surface [Cook and McGeary (1964) suggest that only the most electronegative AI alloys could accomplish this]; the rapidity of the postdeposition cell reactions; or other reasons not yet identified. At the present time, the 4-base material corrosion must be 6-67 considered largely phenomenological in nature.…”
Section: Summary Of Corrosion Rates Of Ai-base Materialsmentioning
confidence: 99%
“…At room temperature, the most anodic aluminum alloys (those with a corrosion potential approaching À 1.0 V vs. SCE) can reduce ferrous ions (Fe 2 þ ) to metallic iron and produce a metallic deposit on the surface of the aluminum. The presence of Fe 2 þ ion also tends to be rare in service; it exists only in deaerated solutions or in other solutions free of oxidizing agents [24]. 6 Cu FIGURE 54.11.…”
Section: C3 Deposition Corrosionmentioning
confidence: 99%
“…The costs (1964 levels) for certain corrosion resistant coatings are shown in TABLE 1 . It has been shown by COOK and MCGEARY that an aluminum cladding alloy containing 1% zinc is better than an alloy of higher zinc content where dissolved iron is present in air-free brine solutions [25]. Iron is deposited at a slower rate at elevated temperatures by the 1% zinc alloy.…”
mentioning
confidence: 99%